2020
DOI: 10.9734/cjast/2020/v39i2230845
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Best Fit Probability Distribution Model for Wind Speed Data for Different Sites of Burkina Faso

Abstract: In order to estimate the power output of a wind turbine, optimise its sizing and forecast the economic rate of return and risks of a wind energy project, wind speed distribution modelling is crucial. For which, Weibull distribution is considered as one of the most acceptable model. However, this distribution does not fit certain wind speed regimes. The objective of this study is to model the frequency distribution of the three-hourly wind speed at ten sites of Burkina Faso. In this context, we compared the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Wind speed distribution is stochastic in nature and can be best expressed as probability distribution function with an acceptable accuracy level (Matthew, 2006 andBoro et al, 2020). To determine the probability distribution of the wind regime, the measured wind speed data was fitted into various probability functions using easyfit software which is an add-on in Microsoft Excel spread sheet, to identify suitable statistical distributions representing the wind speed regime of Heipang village.…”
Section: Wind Speed Data Analysis and Determination Of Weilbull Param...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wind speed distribution is stochastic in nature and can be best expressed as probability distribution function with an acceptable accuracy level (Matthew, 2006 andBoro et al, 2020). To determine the probability distribution of the wind regime, the measured wind speed data was fitted into various probability functions using easyfit software which is an add-on in Microsoft Excel spread sheet, to identify suitable statistical distributions representing the wind speed regime of Heipang village.…”
Section: Wind Speed Data Analysis and Determination Of Weilbull Param...mentioning
confidence: 99%
“…respectively. The power law exponent  is given as (Boro et al, 2020;Tonsie et al, 2021 andManwell et al, 2005):…”
Section: Wind Speed Data Analysis and Determination Of Weilbull Param...mentioning
confidence: 99%
“…One of these drawbacks is the need of determining the values of the parameters appropriately by various types of estimation methods. According to [16,17,[28][29][30], the Kernal density method is the well-known used method.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research studies were observed to determine optimal and/or best distribution, which represents the wind regime of any location (Carta et al , 2009; Morgan et al , 2011; Lo Brano et al , 2011; Boro et al , 2020). However, several authors have found that there is a major difference between the potential of actual wind energy and the estimated wind energy of a location (Deep et al , 2020).…”
Section: Introductionmentioning
confidence: 99%